2013
DOI: 10.1136/bmjopen-2013-003716
|View full text |Cite
|
Sign up to set email alerts
|

Validity of AHRQ patient safety indicators derived from ICD-10 hospital discharge abstract data (chart review study)

Abstract: ObjectiveTo assess if the Agency for Healthcare Research and Quality  patient safety indictors (PSIs) could be used for case findings in the International Classification of Disease 10th revision (ICD-10) hospital discharge abstract data.DesignWe identified and randomly selected 490 patients with a foreign body left during a procedure (PSI 5—foreign body), selected infections (IV site) due to medical care (PSI 7—infection), postoperative pulmonary embolism (PE) or deep vein thrombosis (DVT; PSI 12—PE/DVT), post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 20 publications
0
50
0
1
Order By: Relevance
“…It is possible given this, that the predictive value of the algorithm would be less in populations with lower prevalence of disease. Results will need to be reassessed after introduction of the ICD-10 coding system, which would affect prospective cases of VTE after October 1, 2015[15]. Any algorithm generated for using ICD coding in administrative data will require constant modification and updating over time to account for changes and additions to the ICD codes.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible given this, that the predictive value of the algorithm would be less in populations with lower prevalence of disease. Results will need to be reassessed after introduction of the ICD-10 coding system, which would affect prospective cases of VTE after October 1, 2015[15]. Any algorithm generated for using ICD coding in administrative data will require constant modification and updating over time to account for changes and additions to the ICD codes.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation became apparent during our validation study, as there were insufficient cases of pressure ulcers and fall-related injuries identified during 1 fiscal year. In a large validation study of patient safety indicators using administrative hospitalization data, similar challenges in reaching the target sample size for some indicators were reported 41. Fifteen (5.0%) of the 300 randomly selected records were missing one or more key documents.…”
Section: Discussionmentioning
confidence: 80%
“…We derived our weights using statistical criteria, while clinical knowledge might be needed to determine each comorbidity's value. Since we used codes assigned in routine data, the capture of the comorbidities could be in uenced by other factors, such as physician and nurse documentation, code assignment accuracy, and the possibility that capture of comorbidities is biased towards those for which the Swiss DRG / MDC pays more [46,42]. Moreover, current comorbidity indices are not suitable predictors of patient-centred outcomes like rehabilitation, readmission, fee-for-services while weightings might differ in restricted cohorts, other outcomes and countries [27].…”
Section: Discussionmentioning
confidence: 99%